Environmental issues in a federation: the case of Malaysia - Saleem, Muhammad Yusuf (IIUM Press, 2005)
From a constitutional perspective, the responsibilities over environmental issues cannot be precisely divided between federal and state governments. Environmental problems could only be dealt with successfully, as the Malaysian case exemplify, through a concurrent jurisdiction. The responsibility for the implementation of environmental laws is left to the states which because of their nearness to the source of environmental problems are in a better position to monitor violations. However, interstate environmental problems must be addressed jointly by federal and state governments.